Appreciative learning approach in computer games development class - Eow, Yee Leng; Wan Ali, Wan Zah; Mahmud, Rosnaini; Baki, Roselan (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
The rationale of the study was to understand more about the appreciative learning approach being applied in educational settings, specifically in the computer games development class. The study explored the perception of eight out of the 36 form one students who had gone through computer games development with the appreciative learning approach as a teaching practice for four weeks. Qualitative method was used in the study. The findings indicated that students perceived positively about the environment created within the appreciative learning approach. Nevertheless, there are gaps in the approach being applied as indicated by the students. A few modifications on the approach are suggested in this article for further research in order to accommodate the students' needs and preferences in learning computer games development. Caution is warranted as this article is just part of an action research being carried out.